Autoimmune pancreatitis presenting as obstructive jaundice - Miah, Nurul Amin; Mahbub, Tania; Jahan, Ferdous; Ananna, Mehruba Alam; Arafat, Shohael Mahmud; Jahan, Salma (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
A 71 years cachexic male presented with sign symptoms of biliary tract obstruction. There was a large mass in the head of pancreases with raised CA 19.9. But elevated serum lipase raised the suspicion of paocreatitis. Elevated immunoglobulin IgG4 confmned this case as a auto immune aetiology. Initially there was much difficulty to differentiate auto immune pancreatitis from pancreatic carcinoma but after successful stenting and a course of corticosteroids, patient improved dramatically along with nonnalisation of all the radiological, bio-chemical and immunological parameters.